Multi physics field simulation analysis of different pole slots combined with automotive permanent magnet motors - Guohao LI; Hongbin YIN; Yigang SUN; Zhe ZHANG; Xiangjun BI; Wenjing HU (Journal of Hebei University of Science and Technology)
Aiming at the problems in the design of permanent magnet synchronous motor for vehicles, taking the 8-pole 48-slot and 8-pole 36-slot interior permanent synchronous motors as subject, the influence of different pole-slot combinations on the electromagnetic performance and vibration noise of permanent magnet synchronous motor for vehicles were researched. Firstly, the torque ripples and no-load back electromotive forces of the permanent synchronous motor with different pole-slot combinations were comparatively analyzed in order to investigate the influence of different pole-slot combinations on the electromagnetic performance of the motor. Secondly, the analytical model of electromagnetic force wave was deduced based on Maxwell stress tensor method, and the spatial order and frequency characteristics of the electromagnetic force wave of the motor with different pole-slot combinations were analyzed by the analytical model and the finite element model, respectively. Finally, a multi-physical field coupling model of the motor was established to investigate the effects of different pole-slot combinations on the vibration noise of the permanent magnet synchronous motor. The results show that the 8-pole 36-slot motor is significantly better than the 8-pole 48-slot motor in terms of torque ripple, no-load back electromotive force, and other electromagnetic performances. However, due to the existence of lower spatial non-zero electromagnetic force waves, it is more likely to trigger resonance and generate vibration noise. The analytical results reveal the effects of different pole-slot combinations on the electromagnetic performance and vibration noise of permanent magnet synchronous motors, and provide theoretical references for the selection of pole-slot combinations and subsequent optimization of motor design.